ORGANIZATION OF LEISURE OF RURAL RESIDENTS IN 60-70' OF THE XX - Iskenderov, M E (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the quality of cultural services for all types of population of Dagestan villages, the role of cultural institutions in organizing the use of leisure time and its improvement and the level of consumption of cultural goods within the specified period. The author notes that the rise of the material and cultural well-being of the population and increase of leisure time of agricultural workers contributed to the expansion of all-round contacts between the village and the town and resulted in vigorous activity of large creative organizations of the republic and of the villagers themselves.